THE CAPACITY MULTIPLIER EFFECT IN ASEAN'S ENERGY TRANSITION: HYDROPOWER, SOLAR, AND BIOENERGY DYNAMICS - Try Edi Suwarno; Audina Rahmi; Ananda Sabrida Tora Boru Sinaga; M Bastian; Shahnaz Arianne Amirah (MESP–FEB UNS, 2026)
This study examines the structural associations and comparative capacity multipliers of specific renewable technologies hydropower, solar energy, and bioenergy on the total installed renewable energy capacity in four key ASEAN countries: Indonesia, Malaysia, the Philippines, and Thailand, over the 2015–2024 period. Addressing empirical gaps in the literature on energy mix diversification, this research employs a Fixed Effects Model (FEM) using panel data from the International Renewable Energy Agency (IRENA) to control for unobserved country-specific heterogeneity. To overcome the mechanical accounting identity inherent in regressing an aggregate against its components, this study interprets the estimated coefficients as infrastructural spillover effects rather than strict causal generation outputs. The findings indicate that while all three technologies are positively associated with aggregate capacity expansion, their relative structural impacts differ significantly. Bioenergy exhibits the highest capacity multiplier (1.51), highlighting its critical role in providing dispatchable grid flexibility that accommodates further renewable integration. Hydropower (1.18) serves as a stabilizing baseload anchor, while solar energy (1.05) acts as a highly elastic, near-proportional additive component. Academically, this study refines the econometric understanding of renewable energy expansion in developing economies by quantifying these specific technological synergies. Practically, the findings offer suggestive policy guidance for optimizing capacity investments and grid diversification to support a resilient energy transition toward the region's Net-Zero Emissions targets.